Experiences of health education in physical therapy - Hernández Sánchez, Jacqueline; Lozano García, Leidy Johanna; Murillo Varela, Yurley Andrea (Universidad y Salud, 2016)
Introduction: Health education is a fundamental tool in public health, where the physiotherapists play an important role by either promoting behaviors that protect the health or preventing those that put it at risk. Objective: To identify the characteristics of experiences of HE that physiotherapists carry out worldwide. Materials and methods: A descriptive study was performed by using documentary review of experiences reported in articles published from 1995 to 2014. Results: 30 experiences of physiotherapists as health educators were identified, which were reported in scientific papers. The areas of application were musculoskeletal (20; 69%) and physical activity or exercise (6; 20.6%). There are weaknesses in the theoretical foundations; in addition, traditional methodological strategies such as counseling (24.2%), individual education (21.2%) and the combination of counseling with educational material (9.1%) are used. Printed materials are also widely used. Evaluations carried out are mainly quantitative. Conclusions: There are few scientific publications of experiences about Health education in physiotherapy. Those reported in this article are mainly developed in the muscle-skeletal area. However, there is not a clear theoretical foundation; there is confusion and an indiscriminate use of the term Health education and health promotion. There are normative and training challenges for physiotherapists as health educators; as well as problems to be solved in future research.